Relevance Of Medical Records Management Of Health Care Services Delivery. Case Study Of Jinja Referral Hospital Jinja Municipality. - Boniface Adriko; Fredrick Wandara (Student's Journal of Health Research, 2021)
Background The study sought to investigate the relevance of medical records management on healthcare service delivery in Jinja referral hospital Jinja municipality. The objectives of the study were to describe the present records management practices in Jinja Referral Hospital; find out the existing infrastructure for the management of patient medical records at the Jinja Referral Hospital; determine the compliance of patient medical records management in Jinja Referral Hospital with the relevant national legislative and regulatory framework; find out the security of patient medical records at the Jinja Referral Hospital. Methodology Quantitative and qualitative approaches were employed, the sample was drawn from the service providers and from the healthcare service users. Questionnaires, interviews, and observation were used to collect data. Results The findings showed that Jinja Referral Hospital uses manual records management system in the creation, maintenance, and usage of records. In findings, there were challenges related to misfiling and missing patient folders which sometimes lead to the creation of new patient folders. Also, the study discovered that the time spent in the retrieval of patient folders could negatively affect the timely delivery of healthcare services. Conclusion The creation, maintenance, use, and disposal of medical records at the jinja referral hospital are currently effective under control. This is supported by the fact that there is a consistent system of creating records, classification, and retrieval. Recommendations The study recommended the adoption of electronic records management system as most public healthcare institutions in the country are rapidly shifting to electronic management systems. The use of electronic records management system is believed to be efficiently and effectively promote easy accessibility, retrieval of patient medical records, and allow easy communication amongst the healthcare service institutions and healthcare practitioners.